A Novel NGF Receptor Agonist B355252 Ameliorates Neuronal Loss and Inflammatory Responses in a Rat Model of Cerebral Ischemia - Wang HK; Chen JS; Hsu CY; Su YT; Sung TC; Liang CL; Kwan AL; Wu CC (Journal of Inflammation Research, 2021)
Hao-Kuang Wang,1,2 Jui-Sheng Chen,1,3,4 Chien-Yu Hsu,1 Yu-Ting Su,5 Tzu-Ching Sung,2 Cheng-Loong Liang,1,6 Aij-Lie Kwan,3,7 Cheng-Chun Wu6 1Department of Neurosurgery, E-DA Hospital, I-Shou University, Kaohsiung, Taiwan; 2School of Medicine for International Students, College of Medicine, I-Shou University, Kaohsiung, Taiwan; 3Graduate Institute of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 4Department of Neurosurgery, E-Da Dachang Hospital, I-Shou University, Kaohsiung, Taiwan; 5Department of Obstetrics and Gynecology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan; 6School of Medicine, College of Medicine, I-Shou University, Kaohsiung, Taiwan; 7Department of Neurosurgery, Kaohsiung Medical University Hospital, Kaohsiung, TaiwanCorrespondence: Cheng-Chun WuSchool of Medicine, College of Medicine, I-Shou University, Kaohsiung, TaiwanTel +886-7-6151100-7961Fax +886-7-6155150Email chengchunwu@isu.edu.twIntroduction: Cerebral ischemia is a leading cause of disability and death worldwide. However, an effective therapeutic approach for the condition remains undiscovered. The previously proposed growth factor-based therapy has been inefficient due to its inability to pass through the blood–brain barrier. B355252, a newly developed small molecule, exhibited a potential neuroprotective effect in vivo. However, its exact efficacy in cerebral ischemia remains unclear.Methods: We adopt an endothelin-1 stereotaxic intracranial injection to induced cerebral ischemia in rat. We further conducted 2,3,5-triphenyltetrazolium chloride (TTC) staining, immunofluorescent staining, enzyme-linked immunosorbent assay (ELISA), and behavioral tests to evaluate the efficacy of B355252 in neuroprotection, anti-inflammation, and behavioral outcome improvements.Results: We identified that B355252 could protect ischemic neurons from neuronal loss by attenuating DNA damage, reducing ROS production and the LDH level, and preventing neuronal apoptosis. Moreover, inflammatory responses in astrocytic and microglial gliosis, as well as IL-1β and TNF-α levels, were ameliorated. Consequently, the behavioral outcomes of ischemic rats in neurologic responses and fore paw function recovery were improved.Discussion: Overall, our study verified the in vivo therapeutic potential of B355252. The study findings further support its application in the development of a therapeutic approach for stroke.Keywords: stroke, NGF, B355252, stroke, DNA damage, inflammation, mNSS, cylinder test